Panchagavya and Andrographis paniculata as Alternatives to Antibiotic Growth Promoter on Broiler Production and Carcass Characteristics - Mathivanan, R.; Edwin, S.C.; Amutha, R.; Viswanathan, K. (International Journal of Poultry Science, 2006)
A biological experiment was conducted to study the effect of panchagavya and Andrographis paniculata as alternatives to antibiotic growth promoter on broiler production and carcass characteristics with one hundred and eighty commercial, straight run day-old broiler chicks. The chicks were fed basal diet (T1), basal diet with virginiamycin -20 mg/kg (T2), basal diet with panchagavya -7.5 g/kg (T3), basal diet with A. paniculata -2.0 g/kg (T4), basal diet with probiotics -0.5 g/kg (T5) and basal diet with mannanoligosaccharide (MOS) - 2.0 g/kg from 1 to 28 days and 0.5 g/kg from 29 to 42 days growing period (T6) for 6 weeks period. The result revealed that the mean body weight and weight gain of T6, T5 and T3 groups were significantly (P<0.05) higher as compared to the body weight of T2 and T1 groups at 6 weeks of age. The feed consumption did not show any difference between treatment groups. The FCR was (P<0.05) better in T4 (1.87) compared to T1 and T2 groups, which recorded inferior FCR (2.04 each) at 6 weeks of age. Livability did not differ between treatment groups from 1 to 6 weeks of age. The carcass characteristics, cut-up parts of carcass and sensory qualities of meat did not differ due to dietary supplements.